Whole chromosome painting of B chromosomes of the red-eye tetra Moenkhausia sanctaefilomenae (Teleostei, Characidae) - Scudeler, Patricia Elda Sobrinho [UNESP] (2015)
B chromosomes are dispensable genomic elements found in different groups of animals and plants. In the present study, a whole chromosome probe was generated from a specific heterochromatic B chromosome occurring in cells of the characidae fish Moenkhausia sanctaefilomenae (Steindachner, 1907). The chromosome painting probes were used in fluorescence in situ hybridization (FISH) experiments for the assessment of metaphase chromosomes obtained from individuals from three populations of M. sanctaefilomenae. The results revealed that DNA sequences were shared between a specific B chromosome and many chromosomes of the A complement in all populations analyzed, suggesting a possible intra-specific origin of these B chromosomes. However, no hybridization signals were observed in other B chromosomes found in the same individuals, implying a possible independent origin of B chromosome variants in this species. FISH experiments using 18S rDNA probes revealed the presence of non-active ribosomal genes in some B chromosomes and in some chromosomes of the A complement, suggesting that at least two types of B chromosomes had an independent origin. The role of heterochromatic segments and ribosomal sequences in the origin of B chromosomes were discussed.